Pengaruh Pengangguran, Inflasi, Investasi Asing Langsung, Impor dan Kemiskinan Terhadap Indeks Pembangunan Manusia (IPM) di Indonesia Tahun 1990-2022 - Rosintan S, Lydia; Entaresmen, R Ajeng; Puspitasari, Windhy; Dizar, Shafrani; Nurfitri, Arina; Mailadani, Diah Ayu (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
The study aims to investigate the impact of the Human Development Index in Indonesia from 1990 to 2022 on inflation, unemployment, foreign direct investment, imports, and poverty. An Autoregressive Distributed Lag (ARDL) model is used for the analysis of annual data from 1990–2022 obtained from the United Nations Development Programme and the World Bank (2024). The study's results show that the unemployment variable has a significant negative effect on Indonesia's Human Development Index (HDI) in the short term, but is not significant in the long term. The inflation variable has a significant negative impact on Indonesia's HDI in both the short and long term. Foreign direct investment has a positive and significant effect on Indonesia's HDI in the short term.